Perceptions of Pediatric Critical Care Nurses on the Initiation of a Nursing-Led Feeding Protocol. Issue 4 (December 2015) - Kirk, Angela Hui Ping; Ng, Brenda Sok Peng; Lee, Ang Noi; Ang, Bixia; Lee, Jan Hau
ABSTRACT: Background: Critically ill children frequently receive inadequate nutritional support. Feeding protocols have been shown to facilitate optimal nutritional care. Purpose: We aim to determine the perceptions of critical care nurses with regard to the implementation of a feeding protocol as well as to their preferred teaching methods before introducing this protocol in our pediatric intensive care unit (PICU). We hypothesize that nursing experience and educational level are factors that predict readiness to adopt this protocol. Methods: All PICU nurses were invited to participate in an online survey to investigate their perceptions on protocol implementation and on preferred teaching methods. Statistical analysis was performed using simple logistic regression and the Fisher exact test. Statistical significance was taken as p < .05. Results: Seventy-four nurses completed the survey. Fifty-four (73%) had nursing degrees. Mean duration of PICU experience was 6.2 years (5th, 95th percentile: 1, 15). Three quarters of participants (74%, n = 55) felt that they did not have sufficient knowledge regarding feeding protocols, and 86% ( n = 64) expressed that they were keen to implement a feeding protocol. There was no association between readiness to adopt the feeding protocol with years of ICU experience ( OR = 0.99, 95% CI [0.84, 1.18]) and educational level ( OR = 1.43, 95% CI [0.31, 6.68]). The preferred teaching methods were bedside teaching (61%), didactic lectures (51%), and the distribution of protocol manuals (50%). PICU nurses felt that the advantages of a feeding protocol included standardization of practice, optimization of patient's nutritional intake, earlier initiation of feeding, increased patient safety, and the extension of nursing roles. Perceived disadvantages included inapplicability of the feeding protocol to all patients, lack of flexibility in feeding management, increased confusion, and doctors placing little value on the feeding protocol. Conclusions: This study found that nursing experience and level of education do not significantly affect the readiness of nurses to adopt a feeding protocol. Medical and nursing teams should not shy away from introducing a new protocol although their nurses have little experience or prior knowledge of that protocol. Future studies to investigate the impact of tailoring of educational needs before introduction of a new protocol are necessary to study the overall effectiveness of this teaching before introducing a new protocol in the ICU.